CALCULATION OF GF (P) ELLIPTIC CURVES IN FPGA - Aleksander, Marek; Karpinskyy, Mykola; Litawa, Grzegorz (International Journal of Computing, 2011)
The paper describes a hardware system carrying out point summation on elliptic curves. The implementation of basic function, which is modulo multiplication of huge integrals, is based on Krestenson’s basis. Such a summing unit has been used for hardware implementation of Pollard rho-algorithm. The paper also presents the performance of the mentioned unit.